Seleção de materiais no projeto de máquinas agrícolas - Scheleski, Samuel (2014)
Based on the need to systematize the selection of materials, various methods and tools, all with merits and limitations were developed. The general objective of this work is to select and apply methodologies for selecting materials in the design of agricultural machinery and implements. For this, were performed: a detailed study of the development of this sector of the industry; detection of their requirements; analysis and choice of materials selection methods and tools for their application of agricultural machinery and implements industry, and the development of a case study. Based on the procedures performed, the following conclusions can be reached: (1) the Ashby materials selection methodology was selected because it encourages designers to consider the wide range of innovation opportunities that engineering materials provide. The application of this methodology requires the use of support tools and procedures; (2) the development of a computerized system for selection of materials for the industry proved to be unfeasible under the conditions established in this work; (3) the CES software proved as a good choice of tool to aid the implementation of the selected methodology; (4) the sorting procedures by synthesis and similarity proved to be important to expand the vision of the designers, but better tools than those currently available to the sector of agricultural machinery and implements are needed, and (5) the materials selection methodology chosen by this work can be a major factor for technological innovation in the industry, because it provides a preview of the procedures adopted in other industry sectors and enables companies to master technologies to be implemented in future projects.